An integrated two‐stage anaerobic digestion and biofuel production process to reduce life cycle GHG emissions from US dairies. (18th April 2013) - Coats, Erik R.; Searcy, Erin; Feris, Kevin; Shrestha, Dev; McDonald, Armando G.; Briones, Aurelio; Magnuson, Timothy; Prior, Maxine
Abstract: Over 9 million dairy cows generate an estimated 226 billion kg of wet manure annually in the USA. To help mitigate dairy greenhouse gas (GHG) emissions associated with the degradation of this organic‐rich waste, manure can be processed via anaerobic digestion (AD) to methane and ultimately electricity. This potential value of AD has generated high‐level dairy‐industry support for broad‐scale technology deployment; however, on‐the‐ground AD realization has been impeded by process stability/reliability concerns and poor economics. Considering these challenges but recognizing that AD represents a fundamentally sound manure‐management approach, an interdisciplinary research team has completed proof‐of‐concept investigations on an integrated process that will concurrently improve manure management economics and reduce dairy GHG emissions. The integrated processes center on a two‐stage fermentation/AD system that can generate methane quantity/quality comparable to conventional single‐stage AD. Molecular level investigations confirm that the AD is highly enriched with a unique and synergistic microbial population which yielded a more resilient and stable process. Beyond AD, algae grown on nitrogen/phosphorus‐rich AD supernatant in a photobioreactor yielded biomass concentrations approaching 1.0 g L –1 ; despite an apparent growth lag/inhibition associated with excess organic acids and ammonia, algae growth was significant. Environmental life cycle assessment (LCA) demonstrated that the two‐stage AD configuration coupled with algae production can reduce GHG emissions by approximately 60% as compared with a traditional anaerobic lagoon. The end result is a manure‐management platform that can increase US dairy viability and sustainability. Ongoing investigations are aimed at process refinement with an ultimate commercialization goal. © 2013 Society of Chemical Industry and John Wiley & Sons,  Ltd